2005
DOI: 10.1242/jeb.01472
|View full text |Cite
|
Sign up to set email alerts
|

Human hopping on very soft elastic surfaces: implications for muscle pre-stretch and elastic energy storage in locomotion

Abstract: During hopping in place and running, humans maintain similar center of mass dynamics by precisely adjusting leg mechanics to compensate for moderate changes in surface stiffness. We investigated the limits of this precise control by asking humans to hop in place on extremely soft elastic surfaces. We found that hoppers drastically altered leg mechanics and maintained similar center of mass dynamics despite a sevenfold change in surface stiffness (11-81·kN·m -1 ). On the stiffest surfaces, the legs compressed i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
65
1
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(74 citation statements)
references
References 23 publications
7
65
1
1
Order By: Relevance
“…Crowther et al (29) also have shown that landing on a trampoline is accompanied by "stiffer" joint technique via optimization of the lower impact forces and the elasticity of trampoline. This may improve the transfer of training gains to maximal plantar flexor performance within a specific ankle range of motion (28). Our results indicate that despite any differences in plyometric exercise technique between minitrampoline and ground surface, AT strain adaptations did not differ after a 4-week program in children.…”
Section: Strainmentioning
confidence: 61%
See 3 more Smart Citations
“…Crowther et al (29) also have shown that landing on a trampoline is accompanied by "stiffer" joint technique via optimization of the lower impact forces and the elasticity of trampoline. This may improve the transfer of training gains to maximal plantar flexor performance within a specific ankle range of motion (28). Our results indicate that despite any differences in plyometric exercise technique between minitrampoline and ground surface, AT strain adaptations did not differ after a 4-week program in children.…”
Section: Strainmentioning
confidence: 61%
“…To our knowledge, the effects of plyometric training on an elastic surface on mechanical properties of AT in children have not been previously investigated. Studies in adults reported that subjects who exercise on elastic surfaces first extend the legs and then compress exactly out of phase with surface deformation, increasing leg stiffness and rebound gain (28). Crowther et al (29) also have shown that landing on a trampoline is accompanied by "stiffer" joint technique via optimization of the lower impact forces and the elasticity of trampoline.…”
Section: Strainmentioning
confidence: 99%
See 2 more Smart Citations
“…Of course, the signals travel through neural tracts in humans, but postural adaptations occur faster than neural transmission allows in multicellular organisms much smaller than humans posing shorter neural distances to traverse (e.g., Endlein & Federle, 2013) but also in humans, supporting quiet standing (Marsden, Merton, & Morton, 1983), speech (Kelso, Tuller, Vatikiotis-Bateson, & Fowler, 1984), and hopping (Moritz & Farley, 2004). The connective tissues constitute a hierarchically organized network of small prestressed structures (e.g., at the level of actin filaments composing a single cell's skeleton) nested within larger prestressed structures (e.g., extracellular matrix) nested within yet larger pre-stressed structures (e.g., the fascial encasings around muscles and joints).…”
mentioning
confidence: 99%